Drug Delivery From Poly(ethylene glycol) Diacrylate Scaffolds Produced by DLC Based Micro‐Stereolithography. Issue 1 (December 2014) - Vehse, Mark; Petersen, Svea; Sternberg, Katrin; Schmitz, Klaus‐Peter; Seitz, Hermann; Lendlein, Andreas; Domb, Abraham J.
Summary In this study, the production of poly(ethylene glycol) diacrylate (PEGDA) scaffolds by micro‐stereolithography based on diode laser curing (DLC) is demonstrated. Sample scaffolds are also loaded with acetylsalicylic acid (ASS) as model drug. The samples are immersed in physiological NaCl solution and the drug release characteristics are tested. We show that DLC is a useful technique to prepare drug‐loaded PEGDA scaffolds. The compressive strength of the enriched and DLC‐cured PEGDA is between 7 and 10 MPa, dependent on ASS concentration. ASS free samples reach 14 MPa. The release experiments show an initial burst release phase and the ASS is released within the first 3 hours.